Soil organic carbon and nitrogen in soil physical fractions in woody encroached grassland in South African savannas - Mureva, Admore; Chivenge, Pauline; Ward, David (Commonwealth Scientific and Industrial Research Organisation, 2021)
Woody plant encroachment has transformed land-cover patterns in savannas and grasslands throughout the world, with implications for changes in soil organic carbon (SOC) dynamics. However, our understanding of the effects of woody encroachment on SOC is very limited. In a study of pairs of neighbouring, woody encroached and grassland plots along a rainfall gradient (300–1500 mm mean annual precipitation, MAP) in South African savannas, we quantified the changes in SOC and nitrogen pools to a depth of 100 cm, in three soil physical fractions (coarse particulate organic matter, macroaggregates and silt and clay) and bulk soil. The 0–10 cm soil layer of the 1500 mm MAP site lost 26% of SOC stocks due to shrub encroachment. Contrastingly, the 300 and 350 mm MAP sites gained 24% and 27% total SOC, respectively, due to shrub encroachment. In the soil fractions, the largest changes in SOC, ranging within 2.64–464%, were in the coarse particulate organic matter (unprotected organic matter > 250 μm), and the lowest in the silt and clay fraction (6–32%) across all sites and depths. Soil nitrogen increased across all encroached sites compared with open grasslands, regardless of MAP. For every 1-unit increase in MAP and soil fraction size there was a change of –0.06 and 0.1 SOC (gC/kg soil) in encroached grasslands, respectively. We conclude that shrub-encroached grasslands potentially sequester more C in soils of arid regions than in humid regions. At three of our sites, we were unable to differentiate SOC between encroached and open-grassland soils from bulk soil but could do so from soil fraction analysis. Thus, soil fraction analysis is a more effective way to assess changes in soil C than bulk soil.